GOVERNMENT INITIATIVES AND UNEMPLOYMENT IN SONIPAT DISTRICT, HARYANA: AN EVALUATION - Krishan, Shri; Singh, Rajinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper assesses the effectiveness of government interventions that seek to abate unemployment in Sonipat district, Haryana. The study is concerned with such major programs as the Haryana Employment Generation Subsidy Scheme, Saksham Yuva Scheme, and the Haryana Skill Development Mission (HSDM) and their implementation and effects on the employment rates. Data collected from 2016 to 2019 from 10 government Industrial Training Institutes (ITIs) in Sonipat show that there are issues regarding the course offering that are gender biased, high dropout rates and low placement ratio especially for female trainees. Incentives, such as the Employment Generation Subsidy Scheme to industry in employing local youth, as well as, Saksham Yuva Scheme that disburses unemployment allowance and honorariums to the educated youth, the overall effectiveness is constrained by systemic issues including poor industry linkages, and few course relevance. The paper concludes that in order for these government initiatives to realize their targets, joint efforts are needed to tackle the challenges, which include curriculum reforms, more industry involvement and specific support for the underrepresented groups.